Bankruptcy Law - The National Assembly (2004)
This Law prescribes the conditions and the submission of applications for opening of bankruptcy procedures; the determination of property obligations and measures to preserve property in bankruptcy procedures; the conditions and procedures for restoration of business operation, the procedures for property liquidation and bankruptcy declaration; the rights, obligations and responsibilities of the applicants for opening of bankruptcy procedures, of the enterprises and cooperatives requested for bankruptcy declaration and of the participants in the settlement of requests for bankruptcy declaration